A review of the innovations in metal- and carbon-based catalysts explored for heterogeneous peroxymonosulfate (PMS) activation, with focus on radical vs. non-radical degradation pathways of organic contaminants - Kohantorabi, Mona; Moussavi, Gholamreza; Giannakis, Stefanos (Chemical engineering journal (Lausanne, Switzerland : 1996), 2021)
[Display omitted] •The heterogeneous PMS methods for the elimination of organic contaminants were reviewed.•PMS activation by distinct groups of metallic and carbonaceous catalysts were discussed.•Depending on the catalyst, both radical & non-radical pathways can contribute to contaminants elimination.•Oxygen vacancies and defects, as well as metals’ presence determine the degradation mechanisms.•The leaching of metals from the catalysts was evaluated and compared to assess their suitability. The heterogeneous, sulfate radical-based AOPs (SR-AOPs) have emerged over the last decade as a highly potent technology for the removal of various organic contaminants from water. This review aims to summarize the rapid development of the various heterogeneous catalysts developed for peroxymonosulfate (PMS) activation, destined for the degradation of organic contaminants. We cover catalysts such as metal and bi-metallic oxides, supported noble/non-noble metal catalysts, carbonaceous-based materials, layered double hydroxides, metal organic frameworks, zeolite and perovskite-based catalysts, used as effective activators for the activation of PMS. The radical and non-radical pathways, as well as the role of each radical in the reaction mechanism were discussed in detail. In addition, the physicochemical properties of the catalyst influencing the PMS activation mechanisms were summarized. Finally, a critical comparison of the main categories of heterogeneous catalysts is presented, while the opportunities and shortcomings of their conception and application are also discussed.